Glass Ceiling Effect and Earnings: The Gender Pay Gap in Managerial Positions in Germany - Elke Holst; Anne Busch (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Although there are a variety of studies on the gender pay gap, only a few relate to managerial positions. The present study attempts to fill this gap. Managers in private companies in Germany are a highly selective group of women and men, who differ only marginally in their human capital endowments. The Oaxaca/Blinder decomposition shows that the gender pay gap in the gross monthly salary can hardly be explained using the human capital approach. Adding variableson gender-specific labor market segregation and dimensions of the household and family to the model allows more than two-thirds of the gender pay gap to be explained. However, taking selection effects in a managerial position into account (Heckman correction), the proportion explained decreases to only one-third. This reveals the real extent to whichwomen are disadvantaged on the labor market. In addition, we observe not only that the wages in typical women's jobs are lower than in typical men's jobs but also that women are paid less than men in typical women's jobs. The two-thirds of the gender pay gap that remain unexplained represent the unobserved heterogeneity. This includes, for example, general societal and cultural conditions as well as structures and practices on the labor market and in companies that subject women to pay discrimination and pose an obstacle to them breaking the glass ceiling.
Keywords: J31; J16; J2; 330; Gender pay gap; managerial positions; segregation; Oaxaca/Blinder decomposition; Heckman correction